Optimization CFD study of erosion in 3D elbow during transportation of crude oil contaminated with sand particles - Hayder Al-Khayat, Rasha; A. R. Sadiq Al-Baghdadi, Maher; Aziz Neama, Ragad; Al-Waily, Muhannad (International Journal of Engineering and Technology, 2018)
The oil industry transport the crude oil, but with entrained solid particles. Throughout the production operations of the upstream petroleum, crude oil as well as sand particles corroded from the zones of the formation are regularly conveyed through pipes as a mixture up to the well heads and among well heads and flow stations. In this study, a three-dimensional CFD (Computational fluid dynamics) model has been developed that describes a turbulent transport of solid sand particles as well as crude oil through elbows to predict the erosions rates, where various physical aspects have been combined together including flow turbulence, particle tracking, and erosion simulation. The model has been used to investigate the different parameters that effect for crude oil and sand particles on the erosive wear rate on the pipe walls. Where, the parametric studied for crude oil are viscosity, density, velocity and temperature, also, the parametric studied for sand particles are parti-cles size, particles density and mass flow rate. Therefore, the investigation included evaluated the erosive wear rate on the pipe walls with different parametric studding by using numerical method with CFD technique. This model includes simulation of the three dimensional for turbulent flow, sand particle, and erosion rates modeling. Where, used three methods to evaluating the erosive wear rate on the pipe walls, The Finite Model, The Erosion Rate (E/CRC) Model and The Erosion rate (DNV) Model. Also, in this work can be prediction of the ero-sion position occur on the pipe wall with various parametric effect. Then, the results presented shown that the rate of erosion is increase with increasing the friction between the oil and pipe wall by variable the parametric of crude oil or sand particles. Also, the results are shown that the position of erosion variable dependent on the parametric of oil and sand. Finally, the work shown that the CFD technique is good tool can be used to evaluating the erosion rate and erosion position on pipe wall with various crude oil and sand particles parametric.Â Â